2021
DOI: 10.31964/jkl.v18i1.272
|View full text |Cite
|
Sign up to set email alerts
|

Kecukupan Udara Mempengaruhi Kenyamanan Pada Ruang Kamar

Abstract: Ventilation is the process of exchanging clean air from outside into the room. Good ventilation is able to ensure smooth air circulation. This study aims to determine the relationship of air adequacy with comfort in room space. This research is an analytic study with cross sectional approach. The sample of this study was 30 rooms that used natural ventilation systems. The air change time is calculated from the volume of the room, the height and area of the ventilator, as well as the difference in the temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…7 Previous research showed a relationship between air quality and health problems, such as lung cancer, respiratory disease, heart disease, reproductive disorders and blood pressure. 8 Other previous research 9 showed that there were differences in lung function between bus drivers and indoor workers. From the 65 people, 26.1% of indoor workers and 3.9% of bus drivers experienced pulmonary disorders.…”
Section: Introductionmentioning
confidence: 94%
“…7 Previous research showed a relationship between air quality and health problems, such as lung cancer, respiratory disease, heart disease, reproductive disorders and blood pressure. 8 Other previous research 9 showed that there were differences in lung function between bus drivers and indoor workers. From the 65 people, 26.1% of indoor workers and 3.9% of bus drivers experienced pulmonary disorders.…”
Section: Introductionmentioning
confidence: 94%
“…Tetapi bila stresnya lama dan berat, maka kortisol semakin diproduksi maka akan menekan sistem kekebalan tubuh manusia dan peradangan pada luka semakin meningkat. (Derek et al, 2017) (Maulianti et al, 2021).…”
Section: Pendahuluanunclassified